2013
DOI: 10.1371/journal.pone.0081382
|View full text |Cite
|
Sign up to set email alerts
|

Lung Collagens Perpetuate Pulmonary Fibrosis via CD204 and M2 Macrophage Activation

Abstract: Idiopathic pulmonary fibrosis is characterized by abundant collagen production and accumulation of alternatively activated macrophages (M2) in the lower respiratory tract. Mechanisms as to how alveolar macrophages are activated by collagen breakdown products are unknown. Alveolar macrophages were obtained by bronchoalveolar lavage from 30 patients with idiopathic pulmonary fibrosis (IPF) and 37 healthy donors (HD). Alveolar macrophages were cultured in the presence of collagen type I, III, IV and V monomers w/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 32 publications
4
72
0
1
Order By: Relevance
“…By 28 days, macrophages staining positively for these M2 markers were enlarged, vacuolated, and clustered in thickened alveoli surrounding areas of fibrosis, supporting their profibrotic activity (29,30). Epidemiological evidence, as well as experimental models of idiopathic and chemical-induced fibrosis, have shown that CD163 and CD206 M2 macrophages contribute to fibrogenesis in the lung, kidney, and peritoneum (31)(32)(33)(34)(35). Our findings suggest that they may play a similar role in lung fibrosis after NM exposure; however, this remains to be investigated.…”
Section: Discussionmentioning
confidence: 84%
“…By 28 days, macrophages staining positively for these M2 markers were enlarged, vacuolated, and clustered in thickened alveoli surrounding areas of fibrosis, supporting their profibrotic activity (29,30). Epidemiological evidence, as well as experimental models of idiopathic and chemical-induced fibrosis, have shown that CD163 and CD206 M2 macrophages contribute to fibrogenesis in the lung, kidney, and peritoneum (31)(32)(33)(34)(35). Our findings suggest that they may play a similar role in lung fibrosis after NM exposure; however, this remains to be investigated.…”
Section: Discussionmentioning
confidence: 84%
“…95 When macrophages from the lungs of healthy controls or IPF patients were cultured and stimulated with collagen monomers, the IPFderived macrophages increased expression of profibrotic markers and cytokines, consistent with a classification of the alternative activated state. 96 Although macrophages can clearly promote fibrogenesis, depletion of macrophages during the recovery phase of both toxic liver injury and the lung bleomycin fibrosis models delayed the resolution of fibrosis. 97,98 These findings support that functionally distinct subpopulations of macrophages also play critical roles in recovery.…”
Section: Role Of Inflammatory Cells In Lung Fibrosis Resolutionmentioning
confidence: 99%
“…Despite the abundance of convincing reports associating M2 with fibrosis, mechanistic studies have not been conclusive on the exact role of these cells in fibrosis. M2 and M2-like macrophages are thought to be profibrotic through production of several profibrotic cytokines, notably CCL18 [161][162][163], thus enhancing and prolonging the profibrotic effect of Th2 cytokines. Contrary to this notion, mice lacking arginase 1, a hallmark molecule of M2, are either not protected against [164] or demonstrate exacerbated fibrosis [165].…”
Section: Pdgfmentioning
confidence: 99%